Penggunaan Pecahan Genteng sebagai Agregat untuk Lapis Fondasi Perkerasan Lentur - Nugroho, Soewignjo Agus (Department of Civil Engineering, Diponegoro University, 2006)
Lime has been used for long time as soils stabilizer in sub base and base construction of road. This research studied influence of lime as stabilizer mixed with debris of clay roof as aggregate. Gradation specification is accordance to Bina marga Standard. Lime content used in this research are 0%; 2,5%; 5%; 7,5%; 10%; 12% and 15%.Result of this research shows as lime content increases, California Bearing Ratio (CBR) value for base also increase 80%; 85%; 88%; 91%; 95%; 100% and 110% respectively. For sub base CBR value increase respectively i.e 50%; 60%; 705; 74%; 85%; 90% and 95%.Keywords: stabilization, debris of clay roof, California Bearing RatioPermalink: http://www.ejournal.undip.ac.id/index.php/mkts/article/view/2091[How to cite: Nugroho, S.A., 2006, Penggunaan Pecahan Genteng sebagai Agregat untuk Lapis Fondasi Perkerasan Lentur, Jurnal Media Komunikasi Teknik Sipil, Volume 14, Nomor 2, pp. 112-118]